Marat/Sade : the persecution and assassination of Marat as performed by the inmates of the asylum of Charenton under the direction of the Marquis de Sade /: the persecution and assassination of Marat as performed by the inmates of the asylum of Charenton under the direction of the Marquis de Sade. (2020) - Weiss, Peter, 1916-1982
No abstract available